Positive-sequence virtual-flux control of grid-connected converter during unsymmetrical voltage dips - Francis Mulolani; Matthew Armstrong; Mohammed Elgendy; Ahmed Althobaiti (Institute of Advanced Engineering and Science, 2022)
One of the major problems in direct power-controlled grid-connected voltage source converters is that during voltage dips, the converter current increases to compensate for the reduced grid voltage. The most common voltage dips are unsymmetrical, and they cause unbalance and distortion in the converter current. This paper introduces a new, simple but effective algorithm which limits the current in a direct power-controlled grid-connected voltage source converter during voltage dips. A positive-sequence virtual-flux based control scheme is employed and this makes the current balanced and sinusoidal during unsymmetrical voltage dips. The proposed control clearly demonstrates the performance which is illustrated through various simulations and experimental work. The current during unsymmetrical voltage dips is limited in magnitude and is balanced, with low distortion. The Implementation of this control scheme will enable voltage source converters to stay connected to the grid during voltage dips as required by most grid codes.